INOVASI PELAYANAN PERIZINAN MELALUI PROGRAM "KAIN IKAT" DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU DI KABUPATEN SINTANG - Eka Apriyani; Irna Virnanda; Yuni Dewi Setyowati (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
In essence, this research article discusses the issue of public service in the region by introducing the "Ikat Cloth" innovation implemented by the DPMPTSP of Sintang Regency to streamline the licensing process for business actors. The research employs a qualitative descriptive method, considering five innovation attributes as the research outcome. The results indicate relative advantages in terms of ease of access, alignment with community needs, ease of comprehension, feasibility through the socialization process, and ease of observation reflected in positive changes in licensing services. However, there are occasional challenges due to the weakness of the internet network during implementation. Nevertheless, it is expected that this innovation will assist and facilitate service processes to the community in the future.